Pengaruh Minuman Keras bagi Remaja di Kota Kupang - Rohi, Christine Ekawati; Johannes, Henry Franklin (Sanitation Departement of Health Polytechnic of Kupang, 2024)
Liquor (Alcohol or Ethanol) plays an important role in the culture and life of the people of NTT. The purpose of this study was to analyze the level of alcohol consumption in adolescents and identify the health impacts and behavior of consuming alcohol. The results obtained adolescents consume liquor to look compact (30%). Adolescent dependence on alcohol is 4 x every month. The impact of alcohol on health is liver disorder (30%) and on irritable behavior (25%). The conclusion is that the impact of alcohol for adolescents is that it can cause liver disease and cause changes in behavior to become violent.